Real-time implementation of BESS to Smooth the Output Power Fluctuation of Variable Speed Wind Turbine Generator - Sattar, A.; Al Durra, A.; Caruana, C.; Muyeen, S.M.; Tamura, J. (2014)
© 2014 The Institute of Electrical Engineers of Japan. In this paper, a grid connected variable speed wind turbine (VSWT) PMSG integrated with the NaS-type battery energy storage system (BESS) is modeled in the real-time digital simulator (RTDS) to analyze the performance in a real system. This study is also a part of the future power hardware-in-loop (PHIL) test; therefore, individual components are modeled from the practical standpoint. The wind turbine, power grid, and control system are modeled in the large-time-step main network; however, the wind generator (PMSG), frequency converter (FC), and BESS integrated with STATCOM are modeled in the RTDS VSC small-time-step network to take into consideration the higher-switching-frequency phenomena. The interface transformer is used to connect the different-time-step subnetworks. The option of integrating the anemometer is kept open for a future PHIL test. The simulation results are compared with those obtained from the laboratory standard power system software PSCAD/EMTDC to validate the model developed in the RTDS/RSCAD.